SYNCHRONIZATION OF JUDICIAL PARDON REGULATIONS IN THE INDONESIAN CRIMINAL JUSTICE SYSTEM - syamsuddin, syamsuddin; Efendi, Erdianto; Rahmadan, Davit (Jurnal Ilmiah Advokasi, 2025)
Judicial Pardon is a legal mechanism that grants judges the discretion to decide a case even when the defendant is formally proven guilty. Unlike the traditional criminal law approach, which emphasizes legality and punishment, Judicial Pardon takes into account personal, situational, and social impact factors related to sentencing. This study employs a normative legal method with a synchronization type, analyzing the alignment of laws and regulations both vertically and horizontally. The findings indicate that the synchronization of judicial pardon within Indonesia's penal system is based on three main foundations: philosophical, juridical, and sociological. Philosophically, judicial pardon aligns with the principles of substantive and restorative justice, ensuring proportional punishment while providing room for the rehabilitation of offenders and the restoration of society. The ideal concept of judicial pardon in Indonesia’s future is crucial for establishing a more just, humane, and responsive criminal justice system. Keywords: Judicial Pardon, Criminal Justice Reform, Substantive Justice, Penal Policy, KUHAP